ELECTRIC PROPERTIES OF Mg-SUBSTITUTED LITHIUM IRON SPINEL - L. S. Kaykan; I. M. Gasyuk; V. V. Ugorchuk; J. S. Kaykan; M. Y. Sichka (Vasyl Stefanyk Precarpathian National University, 2014)
Complex impedances of sintered polycrystalline (х = 0.0, 0.1, 0.3, 0.6, 0.8, 1.0) ferrite in the frequency range of 0.01 Hz to 100 kHz were measured at several temperatures in the range of 295-723 K. The complex-plane impedance spectra indicate that the material can be represented by a two-layer leaky capacitor which corresponds to the bulk and the grain boundary phenomena at high and low frequencies respectively. The dependence of impedance and conductivity and dielectric properties on temperature and frequency are discussed.